CHILDHOOD BLADDER STONES-AN ENDEMIC DISEASE OF DEVELOPING COUNTRIES - Lal, Bhamar; Paryani, Jai Pal; Memon, Shafique-ur- Rehman (Journal of Ayub Medical College Abbottabad, 2015)
Background: Bladder calculi are one of the commonest health problems in young children especially in rural and underprivileged areas. Methods: All children of bladder stones operated at District Headquarter Hospital Mithi from July 2009 to June 2012 were included in this cross-sectional study. Data was collected regarding age, sex, address (rural or urban), body weight, duration of breast feeding, weaning, detailed dietary history regarding milk type, volume, amount of water intake, recurrent diarrhoea, urinary tract infection (UTI), family history, and socioeconomic history. Urine analysis, complete blood count (CBC), renal function, ultra sound abdomen, X-ray kidney, ureter, and bladder (KUB) was done in all patients. All patients had cystolithotomy and were followed up till complete recovery. Results: A total of 113 children (97 males and 16 females) operated at District Headquarter Hospital Mithi Tharparker were included in study. All patients belonged to local desert areas of Tharparker. Age ranged from 18 months to 14 year (mean age 8.6 year). Most frequent symptom was difficulty in micturition in 76 (67.25%) patients, urinary retention in 18 (15.9%) and stone with pyuria and fever in 12 (10.6%) patients. Recurrent episodes of diarrhoea (more than 3 episodes per year) in 73(65%) patients, recurrent UTI in 51 (45.6%), family history of stone disease in 6 (5%) and associated rectal prolapse in 3(2.6%) patients. On x-ray KUB 111 (98%) patients had single stone in bladder, 2 (2%) had multiple stones and an associated renal and ureteric stone in 5 (4.5%). Mild anaemia (Hb 7-10 gm%) was seen in 35 (39.55%) patients, moderate anaemia (Hb 5-7 gm %) was seen in 21(24%) and severe anaemia (Hb less than 5 gm%) was seen in 14 (16%) patients. All patients had open cystolithotomy for removal of stones under general anaesthesia. Conclusion: Bladder stones are public health problem. Majority of affected patients were less than 5 years old. Low protein diet, dehydration, use of goat milk and poor socio-economic conditions were major risk factors identified for development of bladder stones. Keywords: Stone disease, endemic, bladder stones